Branding Produk Keripik Ubi Ungu Darum Sebagai Upaya Pembentukan Identitas Visual - retno Setianengsih; Sahrul N (UNIVERSITAS INDO GLOBAL MANDIRI, 2026)
Purple sweet potato chips are a snack with a distinctive flavor and are widely favored by people of various age groups. However, in the marketplace, competition among purple sweet potato chip products is quite intense. Products with attractive visual appearances tend to become market favorites, while those with unappealing packaging and an ordinary brand image are often overlooked. This condition is experienced by Darum brand purple sweet potato chips, which are produced in 2X11 Kayutanam District, Padang Pariaman Regency, West Sumatra. The brand ing design of Darum brand purple sweet potato chips aims to establish and strengthen the product’s visual identity in the minds of consumers in order to increase sales. The design method applied in this project is design thinking, which consists of five stages: empathize, define, ideate, prototype, and test. Data analysis in this design process uses the SWOT analysis method. The results of this brand ing design are expected to produce a consistent visual identity that can create a strong brand image in the minds of consumers. The main medium of this design is a logo presented in the form of a Graphic Standard Manual, while the supporting media include product packaging, employee name tags, uniforms, posters, X-banners, aprons, stickers, social media content, and a neon box. The final design is tested on the client’s product to evaluate whether the brand ing successfully creates a positive brand perception and attracts consumers to purchase Darum brand purple sweet potato chips.